2011
DOI: 10.1111/j.1447-0349.2010.00716.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental health nursing in Jordan: An investigation into experience, work stress and organizational support

Abstract: Changes in mental health services have an impact on the role and practice of mental health nurses. The purpose of this study was to examine Jordanian mental health nurses' experiences of providing mental health care, their work-related stress, and organizational support received. A descriptive correlation design was used. Data were collected using self-report questionnaires from 92 mental health nurses in Jordan. The result of this study revealed that mental health nurses shared a high level of agreement on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 38 publications
2
36
0
8
Order By: Relevance
“…The decision to include nurses from different levels of the hierarchy is consistent with other research (Hamdan‐Mansour et al . ) that has shown that the inclusion of multiple perspectives can enhance the richness of the material collected.…”
Section: Methodsmentioning
confidence: 99%
“…The decision to include nurses from different levels of the hierarchy is consistent with other research (Hamdan‐Mansour et al . ) that has shown that the inclusion of multiple perspectives can enhance the richness of the material collected.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Moustaka & Constantinidis [4] maintained that occupational stress arises from physical, psychological, and social aspects of the work environment and that high level of stress results in staff burnout and turnover and adversely affect quality of nursing care. Occupational stress, interchangeably referred to as work stress, among nurses found to associate with negative outcomes in the workplace including lower job satisfaction [5] [36], high rate of turnover, burnout, lower productivity and absenteeism [4] [37]. Work stress has also found to disrupt nurses' physical, psychological, and social wellbeing [38] [39].…”
Section: Job Demand As a Source Of Stress In Nursing Professionmentioning
confidence: 99%
“…Nursing profession is a stressful and highly demanding profession; where most of the nurses reported high to very high job stress or strain [1] [2] [3] [4] [5]. An International Labor Organization [6] study indicated that nursing profession is ranked 12 among the top 20 stressful occupations.…”
mentioning
confidence: 99%
“…In many countries, there is great interest in the work environment and well-being of staff members in psychiatric care contexts [1,2,3,4,5,6,7]. The phenomenon of the psychosocial work environment and its constituents have been described in several different ways and often include a multitude of aspects, such as organisational climate and culture, work demands, work control, leadership empowerment and support, and co-worker support and collaboration [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The literature in the area of stress in general is voluminous, and several studies from various countries have reported on moderate to high levels of stress, strain, and burnout among psychiatric nurses [3,4,5,20,22]. The impact of Perceived Stress on the psychosocial work environment in psychiatric care, however, has been scarcely researched and needs to be further investigated.…”
Section: Introductionmentioning
confidence: 99%